Assessment of Soil Carbon Stock and Important Physicochemical Properties in relation to Land use Patterns in Semi-arid Region of Rajasthan, India - Garima Sharma (Journal of the Indian Society of Soil Science, 2022)
A study was conducted to assess the influence of land use type on soil organic carbon (SOC) and relatedsoil properties in the Pushkar valley region of Rajasthan. The ANOVA revealed that within 0-10 cm soildepth, the mean amount of organic carbon (%) and the mean amount of organic carbon stock (t ha-1) weresignificantly influenced by land use types (F=184.54, p fallow land (20.17 t ha-1). The minimumbulk density (1.32 Mg m-3) was recorded at the surface of forest soil, whereas the maximum bulk density(1.47 Mg m-3) was found in the lowest layer of the cultivated land. The present study also revealed a strongnegative correlation (p